Penguatan Nilai Multikultural Pada Kurikulum Pesantren - Muhammad Anas Ma`arif; Arifin Arifin (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2022)
This article aims to determine the extent to which the planning, implementation, and evaluation of the multicultural-based curriculum at the Sabilul Muttaqin Foundation. The research method used is qualitative with a case study approach. The technique of collecting data in the form of observation, interviews, and documentation, then analyzing and drawing conclusions from the field data obtained. The findings of this research are: Planning for a Multicultural-Based Islamic Boarding School Curriculum at the Sabilul Muttaqin Foundation: a) The teacher council as curriculum planner first becomes a good role model for students b). There is approval from the chairman of the Foundation. c) Conducting deliberation d) The prepared curriculum can be a forum for students to understand multicultural values. 2) implementation of the multicultural-based pesantren curriculum at MTs Sabilul Muttaqin, namely; a) Instilling multicultural values b) Implementing policies that are in line with the multicultural curriculum c) Supervising and encouraging all activities d) Adjusting the lesson plans that have been prepared with the curriculum e) Preparing exciting techniques and methods f) using classical and modern systems, with Arabic and English as the language of instruction g) combining the national education curriculum and the pesantren curriculum, and 3) Evaluation of the multicultural-based pesantren curriculum at the Sabilul Muttaqin foundation, a) Curriculum evaluation carried out in stages b) knowing the success of achieving educational goals, c) the mechanism for implementing the evaluation curriculum directly and at the end of the school d) holding monthly meetings e) evaluations carried out by the teacher council when learning takes place, and curriculum meetings participate.